Women in Local Governance: Citizen Perceptions of Female Leaders’ Servant and Ethical Leadership and Their Citizenship Behaviors in Kathmandu, Nepal - Aryal, Bindu Tandon; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
The introduction of the reservation system in the local governance system of Nepal has signifi cantly increased female representation in ward offices. This high number now offers a valuable opportunity to understand how citizens perceive the leadership behaviours of these elected women. This study investigates how perceptions of citizens about Servant Leadership (SL) and Ethical Leadership (EL) of female ward representatives influence the Organizational Citizenship Behaviour of citizens with the Public Service Motivation (PSM) as a mediator. Using simple random sampling, data was collected from 458 residents of Gokarneshwor Municipality, Kathmandu filtering only those respondents who were familiar with the elected female ward leaders. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data which showed strong explanatory power with 78.6% of variance in the citizens’ OCB (R² = 0.786). Th e results revealed that direct effects of SL (β = 0.511, p < .001) and EL (β = 0.444, p < .001) were significant and they positively predict OCB. Further, PSM also strongly predicts OCB (β = 0.505, p < .001) and partially mediates the influence of both styles of leadership. The results highlight the fact that women leaders are not just numbers to fill up the seats via reservation, but their action and approach to public service delivery have impressed the citizens and hence them being in the local government offices representing their wards and providing services to general public is a clear indication of the country marching towards gender equality. This study clearly backs the reservation system as citizens perception on their women political leaders elected under the reservation system is indeed a positive one.